2009
DOI: 10.1001/archfacial.2008.511
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Crosseal Fibrin Sealant (Human) in Rhytidectomy

Abstract: Crosseal is efficacious in reducing ecchymoses after rhytidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…included patients having central neck dissection, whereas Vidal‐Perez et al . included patients having central and lateral neck dissections), one at lateral neck dissection, one at parotidectomy and five at rhytidectomy . Only six of the included studies reported a sample size calculation and only three of these reached the planned sample size.…”
Section: Resultsmentioning
confidence: 99%
“…included patients having central neck dissection, whereas Vidal‐Perez et al . included patients having central and lateral neck dissections), one at lateral neck dissection, one at parotidectomy and five at rhytidectomy . Only six of the included studies reported a sample size calculation and only three of these reached the planned sample size.…”
Section: Resultsmentioning
confidence: 99%
“…2 A previously described alternative sutureless technique was complicated by wound dehiscence, tarsal buckling, and undercorrection, and has since been largely abandoned. [5][6][7][8][9][10][11][12] The safety of Müller's muscle-conjunctiva resection ptosis repair using fibrin sealant for wound closure has previously been reported in the literature. The combination of these components produces a fibrin clot, which is adhesive to human tissues.…”
mentioning
confidence: 99%
“…Case reports,11,12,31 large series,13,14,3235 and randomized prospective trials27,36,37 support the value of using fibrin sealant in rhytidectomy. Several investigators question some of the reported advantages of this material 3840.…”
Section: Fda Approved Fibrin Sealant For Rhytidectomymentioning
confidence: 92%
“…In a small, FDA sponsored, single institution, randomized, prospective trial of patients (n = 9) with pressure dressings applied to all patients, reviewers blinded to treatment, and randomly varying the side of the face treated with fibrin sealant (Crosseal; Omrix, Brussels, Belgium),37 a significant reduction in the treated patient sides was found for ecchymosis score, 4.5 versus 6.2 ( P < 0.01). No significant reductions in hematoma or seroma formation were found.…”
Section: Fda Approved Fibrin Sealant For Rhytidectomymentioning
confidence: 99%